Global warming potential of rice (Oryza sativa)-wheat (Triticum aestivum) cropping system of the Indo-Gangetic Plains - D K GUPTA; A BHATIA; A KUMAR; B CHAKRABARTI; N JAIN; H PATHAK (The Indian Journal of Agricultural Sciences, 2015)
The Indo-Gangetic plains (IGP) of India are dominated by rice (Oryza sativa L.)-wheat (Triticum aestivum L.) cropping system (RWCS). Soil, climate, intensity and methods of rice and wheat cultivation differ in different parts of the IGP. So, the emission of greenhouse gases (GHG) will also differ. Present study quantified GHG emission and global warming potential (GWP) of RWCS of Haryana (Upper-IGP) and Bihar (Middle-IGP). A survey of rice-wheat growing farmers in three districts of Haryana (Kaithal, Karnal and Kurukshetra) and Bihar (Begusarai, Bhagalpur and Khagaria) was conducted. The survey data was used as inputs in InfoRCT model to simulate GHG emission in ricewheat systems of different districts. The selected areas in the IGP significantly differed in nitrogen, water and tillage inputs resulting in differences in emission of methane (CH4), nitrous oxide (N2O) and carbon dioxide (CO2) and the GWP. The simulated average GWP of conventional RWCS was 4268±179 kg CO2 equivalent/ha in Middle-IGP (Bihar) and 10605±680 kg CO2 equivalent/ha in the Upper-IGP (Haryana). However, with use of resource conserving technologies (RCTs) such as system of rice intensification (SRI), direct-seeded rice (DSR) and zero tillage wheat (ZTW), there was lowering in GWP than conventional puddled transplanted rice and tilled wheat. Rice had higher contribution than wheat towards GWP in both the states. The continuous flooded puddled transplanted rice (CFTPR), use of electric pump for irrigation and application of high amount of nitrogenous fertilizer were identified as main contributors of GWP. The site-specific intervention of RCTs may be recommended to reduce the emission of GHG in the RWCS in the IGP.